Mexico : Selected Issues. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper analyzes the impact of Mexico's energy reform on hydrocarbons production. These reforms aim to increase oil and gas production by eliminating the state oil company's (PEMEX) monopoly on exploration and production of hydrocarbons, while retaining the prime directive that these resources are the property of the Mexican nation. This paper focuses on the nature of reforms and what problems these reforms are addressing. It presents illustrative production scenarios for crude oil and natural gas and estimates the commensurate investment costs and foreign direct investment associated with each scenario. The paper also examines the markets for the distribution of natural gas and electricity.